Application of liquid glass (SiO2) on textile products - Dogan, O.; Dag, R. (Lviv Polytechnic Publishing House, 2016)
Liquid SiO2 solutions produced by silicon-based nano- powder are covered on the fabric surface by using spray method. Fabric surfaces were coated at the room temperature in air with the different spray nozzles. Surface analysis of the coated fabric was performed by using Contact Angle and SEM pictures. According to the Contact Angles measurements, the coated fabric surfaces showed hydrophobic character between 126 and 146 degrees, and the SiO2 particles sticked to the fabric fibers as seen from SEM picture.
Keywords: SiO2 nano glass; nano coating; nanotechnology; advanced materials; textile products